Relationship Between Risk Factors For Ischemic Stroke and Vitamin D Level - Gulin Morkavuk; Kübra Işık; Guray Koc; Refah Sayin; Alev Leventoglu (Van Tıp Dergisi, 2021)
INTRODUCTION: Stroke is a public health problem as it is the second most common cause of death and the first most common cause of morbidity in the population over 60 years of age. Hypertension, diabetes, smoking, and obesity are known as the most critical risk factors. However, investigation of preventable and treatable unknown risk factors continues. Recent studies have reported that vitamin D reduces the risk of cardiovascular diseases. This study aimed to examine the relationship between risk factors and vitaminD levels in patients with ischemic stroke. METHODS: 54 patients were included in the study. The sociodemographic characteristics of the patients and the results of the examinations for the etiology of stroke were retrospectively analyzed from the hospital information system. VitaminD levels of patients were compared with those with and without recurrent stroke, pre-stroke treatment, hypertension, diabetes mellitus, coronary artery disease, atrial fibrillation, normal doppler USG, cardiac tests results. RESULTS: 24 of the 54 patients were female, 30 were male. There was no significant difference in vitaminD levels between those who had antiaggregant/anticoagulant treatment before the stroke and those who did not. VitaminD level was found to be lower in the group with hypertension compared to the group with no hypertension. VitaminD level was found to be statistically significantly higher in the group with normal carotid Doppler ultrasonography results. Correlation analysis revealed a positive correlation between HDL level and vitamin D level. DISCUSSION AND CONCLUSION: When the results of this study is considered, we can say that vitaminD deficiency and insufficiency are important cardiovascular risk factors.